Evaluation of the knowledge in seismotherapy of the nurses of the neuropsychiatry pole - H. El Kefi; W. Kabtni; S. Borgi; I. Gafsi; C. Bencheikh; A. Oumaya (European Psychiatry, 2022)
Introduction Electroconvulsive therapy, also known as seismotherapy or electroshock therapy, consists of passing an alternating current of variable intensity between two electrodes placed on either side of the patient’s skull to create a generalized convulsive seizure with therapeutic effects.